2013
DOI: 10.1002/jbm.a.34966
|View full text |Cite
|
Sign up to set email alerts
|

Effect of geometry and microstructure of honeycomb TCP scaffolds on bone regeneration

Abstract: In recent years, artificial biological materials have been commonly used for the treatment of bone tissue defects caused by trauma, tumors, or surgical stress. Although tricalcium phosphate (TCP) is a promising absorbent bone tissue reconstruction biomaterial, it has been reported that its biocompatibility and osteoconductivity depend on its preparation method and sintering temperature. In addition, although it is thought that the microenvironment produced by the extracellular matrix plays an important role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…It is generally regarded that the minimum pore size of 100 μm supports bone ingrowth, and the size >300 μm is more beneficial for vascularization . Many studies demonstrated that the channel‐like pores facilitated fast vascularization and cell growth, thus conducing to better new bone regeneration . Previously, we originally fabricated honeycomb β‐TCP scaffolds through an extrusion method featuring high production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally regarded that the minimum pore size of 100 μm supports bone ingrowth, and the size >300 μm is more beneficial for vascularization . Many studies demonstrated that the channel‐like pores facilitated fast vascularization and cell growth, thus conducing to better new bone regeneration . Previously, we originally fabricated honeycomb β‐TCP scaffolds through an extrusion method featuring high production.…”
Section: Introductionmentioning
confidence: 99%
“…38,39 Many studies demonstrated that the channel-like pores facilitated fast vascularization and cell growth, thus conducing to better new bone regeneration. [40][41][42][43] Previously, we originally fabricated honeycomb β-TCP scaffolds through an extrusion method featuring high production. The obtained scaffolds featured channel-like macropores, uniform pore structure and readily controllable macropore size.…”
Section: Introductionmentioning
confidence: 99%
“…We have already succeeded in developing new honeycomb β-TCP which has a through-and-through hole penetrating the material in order to overcome the problems mentioned above. It was found that histologically the honeycomb β-TCP had high biological activity, when β-TCP at varied sintering temperatures was embedded into an experimental animal model 18 . In this study, we reproduced an extracellular microenvironment using new β-TCP that contained through-and-through holes and varied pore size in each material and investigated the effect of the extracellular microenvironment formed by honeycomb β-TCP on bone tissue formation.…”
Section: Introductionmentioning
confidence: 99%
“…An interconnected porous structure is attractive for bone substitutes because bone tissue and cells can penetrate the bone substitute . Furthermore, microporous structure should play an important role in cell growth and differentiation, similar to the niche environment or microenvironment produced by the extracellular matrix . Among many porous structures available, the honeycomb (HC) structure is unique due to its fully interconnected and oriented pores having the same pore size, and shows high mechanical strength in the direction of the pores …”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25] Furthermore, microporous structure should play an important role in cell growth and differentiation, similar to the niche environment or microenvironment produced by the extracellular matrix. [26][27][28][29][30][31][32][33] Among many porous structures available, the honeycomb (HC) structure is unique due to its fully interconnected and oriented pores having the same pore size, [34][35][36][37][38][39] and shows high mechanical strength in the direction of the pores. 40 Therefore, the feasibility to fabricate CO 3 Ap HC was studied herein, based on the HC extrusion method.…”
Section: Introductionmentioning
confidence: 99%